Vascular Endothelial Growth Factor in Tear Fluid as a Marker of Treatment Effectiveness in Patients with Diabetic Retinopathy and Hypertensive Disease - D. Z. Jalalova; D. A. Uralov (American Journal of Biomedicine and Pharmacy, 2025)
Diabetic retinopathy is a severe microvascular complication of diabetes mellitus and a leading cause of blindness. Intensive glycemic and blood pressure control slows its progression [1,2]. Elevated cholesterol and triglyceride levels increase the risk of vision loss. Studies (FIELD, ACCORD-Eye) have demonstrated the effectiveness of fenofibrate in systemic therapy for retinopathy, reducing the need for laser treatment and vitrectomy. The mechanisms of action include both lipid and non-lipid effects: apoptosis reduction, decreased oxidative stress and inflammation, strengthening of the blood-retinal barrier, and neuroprotection [3,4,5].